Universal Health Coverage: Internalisasi Norma di Indonesia - Cipto Rizqi Agung Saputro; Fenny Fathiyah (Jurnal Jaminan Kesehatan Nasional, 2022)
Access to health care is part of human rights. As an effort to realize this right, the United Nations (UN) and World Health Organization (WHO) initiated a program that is Universal Health Coverage (UHC). UHC, as a program that seeks to be implemented, cannot be separated from the values and benefits it stands for. This research aims to see the extent to which the internalization of UHC norms is implemented in Indonesia and the actors involved. This research uses a descriptive method with a qualitative approach. To achieve the research objectives, this study uses the concept of norm diffusion proposed by Finnemore & Sikkink and the concept of norm localization by Amitav Acharya. Through this research, it was found that UHC is a new norm in the international world that is trying to spread throughout the world. It was also found that the Government of Indonesia has internalized the norm and has entered the third phase, which is the final phase in the norm internalization process with the appointed designated local service, namely BPJS of health.